PENGEMBANGAN MEDIA BERBASIS POWER POINT UNTUK PENYAJIAN BAGIAN-BAGIAN TUMBUHAN MELALUI CTL DI KELAS IV SD - Siti Rahmah Al-Khairani Harahap; Ahmad Sukri Nasution (JURNAL PENDIDIKAN DAN PEMBELAJARAN TERPADU (JPPT), 2021)
The objective of this research are (1) to developing learning media based on power point to presentation parts of plant that pointful used in grade IV Elementary School (2) to developing learning activities parts of plant through CTL using power point in grade IV Elementary School. The type of this research was Development (Research and Development) using Model ADDIE model (Analysis, Design, Development, Implementation, Evaluation), this research only done until Development phase. This research was conducted in public elementary school 136541 Tanjungbalai. Instrument for this research were interview and questionnaire. Subject in this research were material expert, media expert and response of students. Technic of data analysis used qualitative and quantitative analysis. Data analysis result obtained validity within the range V≤1,5 (Not Valid) and 3,5≤V≤4 (Very Valid). Assessment from material expet had an average through the aspect of content 3.66, aspect of language 3.66, aspect of presentation 3.25 and aspect of graphic 3.75. Assessment from media expet had an average through aspect of sound 3.5, aspect of language 3.5 and aspect design 3. Assessment from class representative in grade IV elementary as random that are Egi Febriansyah 3.8, Fajar Sitorus 3.3, and Albert Fikri Siregar 3.1. The result could conclude that learning media was “Valid” and learning media based on Power Point was pointful used or applied in learning process. Keyword : Learning Media, Power Point, Natural Science, Parts of Plant